KAJIAN HUKUM KASUS KORUPSI BANTUAN SOSIAL DARI KEMENTERIAN SOSIAL BERDASARKAN ALIRAN POSITIVISME - Kartika Cahyaningtyas; Eko Ari Wibowo (JURNAL SUMBER HUKUM, 2024)
This research examines and analyzes cases of corruption in social assistance from the Ministry of Social Affairs during the Covid-19 pandemic based on analysis using positivism. This is because of the conditions during the Covid-19 pandemic, where many people around the world are suffering and the economy is unstable, but one of the officials from the Ministry of Social Affairs committed corruption during the Covid-19 pandemic. Positivism is a school that believes that law comes from applicable regulations, so what are the consequences of an official from the Ministry of Social Affairs committing corruption during the Covid-19 pandemic. The method used is normative research with a problem approach, namely the case approach and statutory approach. The results of this research show that perpetrators who commit acts of corruption during the Covid-19 pandemic can receive the death penalty. The provisions that apply are in Law Number 31 of 1999 concerning the Eradication of Corruption Crimes consisting of Article 11, Article 12 letter a or Article 12 letter b, Article 12 letter (i), 5 paragraph (1) letter a or Article 5 paragraph (1) letter b, and Article 13 and there are other regulations in the Criminal Code, namely Article 55 paragraph 1 to 1. Keywords: Corruption, Covid-19 Pandemic, Ministry of Social Affairs, Positivism, Death Penalty